Analysis of Flow Patterns in High‐Gravity Equipment Using Gamma‐Ray Computed Tomography. Issue 7 (7th March 2019) - Groß, Kai; Bieberle, André; Gladyszewski, Konrad; Schubert, Markus; Hampel, Uwe; Skiborowski, Mirko; Górak, Andrzej
Abstract: The capacity of today's gas‐liquid contacting equipment such as tray or packed columns is limited by the gravitational‐driven liquid flow. Intensified equipment applying centrifugal force offers great potential for enhancing the mass transfer and for reducing equipment size. Yet, detailed knowledge about the liquid flow inside rotating packings is scarce due to limited accessibility with conventional measurement systems. In this study, a gamma‐ray computed tomography is employed to quantify the liquid hold‐up and its distribution in the moving packing. Abstract : A non‐invasive CT‐based imaging technique was applied to an intensified gas‐liquid contactor. Due to synchronization of the CT system and the rotating packed bed, angle‐resolved reconstructions could be obtained. Furthermore, detailed evaluation of structural effects of packing and rotor internals on the liquid distribution could be revealed.